STRUCTURAL DESIGN OF BARANANGSIANG SMART STATION TERMINAL - Susanto, Gallend
Baranangsiang Smart Station Terminal is a fictional building, designed as a renovation for the current existing station to minimize congestion at Baranangsiang, Bogor. The main terminal consists of 2 buildings connected by a circular ramp between both buildings. It has building 1 as departure area and building 2 as office area. Building 1 has the highest elevation of 14.5 meters with 3 floors while Building 2 has the highest elevation of 13 meters with 2 floors. This final focuses on designing structural scope of the buildings based on SNI 1727:2020 on Minimum Design Loads and Related Criteria for Buildings and Other Structures, SNI 1726:2019 on Procedures for Earthquake Resistant Planning for Building and Non-Building Structures, and SNI 2847:2019 on Requirements for Structural Concrete for Buildings. The building structure is designed using reinforced concrete material. The opted structural system is special moment frames system. The building was modelled using ETABS 2018 version software. Structural analysis was carried out in which the ground floor of the structures is assumed to be fixed. asumsi penjepitan pada lantai dasar. From structural analysis, it was obtained that the structure of building 1 has vertical irregularity type 2 while structure of building 2 has horizontal irregularity type 3,5 and vertical irregularity type 2. The result of reinforcement detailing consists of 11 types of beam, 5 types of column, and 3 types of slab.